2005
DOI: 10.4321/s1130-01082005000900002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antitumor activity of interleukin-12 in an experimental murine model of colorectal cancer induced by 1,2 dimethylhydrazine (DMH)

Abstract: Objective: interlukin 12 (IL-12) is a cytokine that may enhance the proliferation and cytotoxic activity of T lymphocytes and natural killer (NK) cells. A relationship between extensive intratumoral infiltration of NK cells and longer survival rates in colorectal cancer (CRC) patients was previously noted. Preliminary evidence suggests that the combined administration of IL-12 and IL-2 may produce additive immunomodulatory activity. The purpose of this study was to determine whether the systemic administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Mice received five weekly DNA injections of the TERT-LTB fusion construct. DMH treatment did not compromise the immune responsiveness in mice (28), and in agreement with previous findings, we found that the immune responsiveness against mTERT [198][199][200][201][202][203][204][205] 6 in DMH treated; n = 6 mice/group).…”
Section: Resultssupporting
confidence: 78%
“…Mice received five weekly DNA injections of the TERT-LTB fusion construct. DMH treatment did not compromise the immune responsiveness in mice (28), and in agreement with previous findings, we found that the immune responsiveness against mTERT [198][199][200][201][202][203][204][205] 6 in DMH treated; n = 6 mice/group).…”
Section: Resultssupporting
confidence: 78%
“…Another study showed that dendritic cells pulsed with lung cancer cell lysate could induce tumor specific immune response and showed promising clinical outcomes in patient with lung cancer (Han et al, 2006). The antitumor activity of recombinant IL-12 was tested in a variety of murine tumor models where it causes tumor regression and prolonged the survival of tumor (Coca et al, 2005). Other clinical studies report that the antitumor effect of IL-12 gene-transduced DC vaccine on melanoma, adenocarcinoma of kidney and neuroglioma (Kikuchi et al, 2001;Marten et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ya pı lan ça lış ma lar da, ko lon kan se ri ge li şi mi ne ek ola rak DMH'nin, hay van lar üze rin de ba zı toksik et ki ler gös ter di ği de ifa de edil miş tir. DMH'nin 20 mg/kg ola rak ve ril di ği bir ça lış ma da, ilk 16 hafta bo yun ca, hay van la rın %53'ünün öl dü ğü ra por edi lir ken 16 ay nı doz ve ri len baş ka bir ça lış ma da, DMH en jek si yo nun dan son ra fark lı za man lar da 210 fa re nin 13 ta ne si nin öl dü ğü be lir til miş tir. 17 Tü mör olu şu mu na bağ lı ola rak ve DMH'nin tüm bu tok sik et ki le rin den do la yı DMH en jek te edi len hay van lar da ki lo kay bı da göz len miş tir.…”
Section: Tar Tiş Maunclassified